The evaluation and optimization method of major events-driven polluted coastal zone renewal: a case of the polluted coastal zone in the Dalian Barracuda Bay Stadium Area - Gu, Meng; Guo, Qi; Yang, Kexin; Jiang, Bin; Yu, Yang (Frontiers in Environmental Science, 2023)
Introduction: Coastal zone pollution leads directly to a series of local ecological, economic, and social damages. The renewal of polluted coastal zones is a comprehensive challenge that includes the degeneration of ecological services, the decrease in urban livability, and the increase in maintenance costs. Since current ecological management pays more attention to relevant technologies and investments, it plays a limited role in effectively and quickly executing the renewal of polluted coastal zones. Nature-based solutions (NbS) aim to improve regional ecological restoration and renewal by balancing multiple interests such as ecology, economy, and society. Therefore, NbS is an effective way to address this comprehensive challenge. Current studies on NbS are actively exploring the theoretical framework and practice process of solving complex social challenges through an ecological approach. Methods: As an implanted production process, major events could provide robust policy support and continuous economic backing, which makes this an effective solution for challenges such as a lack of support and ineffective guarantees. This paper was centered around the goal of NbS theory, which is achieving comprehensive benefits, and establishing the Social-Economic-Ecological Systems framework (SEESs) that is driven by major events to achieve the renewal of polluted coastal zones. Results: The main objective of this study was to investigate the renewal-driving potential of major events in facilitating the restoration (renewal) of coastal ecosystems from the perspective of NbS. Specifically, it aimed to explore how major events promote the renewal of polluted coastal zones, thereby fostering local socioeconomic advancements and enabling regional sustainable development. Driven by hosting the 2023 China Asian Cup, the renewal of the polluted coastal zone in the area around Dalian Barracuda Bay Stadium was studied. Three subsystems and 12 indexes were selected as evaluation indexes of polluted coastal zone renewal driven by major events. Furthermore, using the entropy weight method, we constructed an evaluation system of polluted coastal zone renewal benefits driven by major events, then verified the synergistic effect of the major event on the social, economic, and ecological recovery of the polluted coastal zone. Moreover, we evaluated the change in the comprehensive scores of the polluted coastal zone from 2018 to 2021 under the impact of the 2023 Asian Cup. The spatial and temporal patterns of each subsystem and index were also discussed. Discussion: Finally, we proposed methods for the optimization of the renewal of urban coastal zone pollution driven by major events and provide solutions to cope with the negative impact of epidemics, strikes, and war throughout the process.